Construction of protocol for the elaboration of Extract of Cucumis anguria L. (Research, Society and Development, 2021)
This study aimed to build a protocol for the elaboration of the hydroethanolic extract of Cucumis anguria L. This is a methodological study, based on laboratory tests to obtain extracts. The method was tested by hydrothanbolic mother tincture, by macerated, according to the Pharmacopoeia. Moreover, the hydrodistillation method for essential oil extraction was tested. For the production of hydroethanolic extract, by mother tincture, fresh fruits were added to the glass jar containing the liquid extractor alcohol 70ºGL. The vial was protected from any alteration of the external medium, being stirred daily, for 30 days until it was taken to the rotary evaporator. The extractor liquid was eliminated in its proportion of 70% of the initial graduation, leaving the final extract, with characteristics of a viscous liquid. For the extraction of essential oil, by hydrodistillation, the whole fruit in natura and the seeds were used. After being inserted into the balone, waited for the boiling time, starting the timer of 4 hours. At the end of time, the presence of suspended oil molecules cannot be observed, which indicates that they do not have enough oil for this type of method. In the Pharmacopoeia there is no experimental test or method of extraction of this fruit, which shows the importance of making a protocol. Therefore, it was identified that the extraction of Cucumis anguria L. by the method of mother tincture, hydroethanolic, by maceration, with the liquid extractor alcohol 70ºGL, proved to be viable for experimental use.